OP0055 EFFICACY OF CANAKINUMAB, ON A REDUCED DOSE OR A PROLONGED DOSE INTERVAL WITHOUT CONCOMITANT CORTICOSTEROIDS AND METHOTREXATE, IN PATIENTS WITH SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS. (June 2019) - Quartier, Pierre; Alexeeva, Ekaterina; Wouters, Carine; Calvo, Inmaculada; Kallinich, Tilmann; Wulffraat, Nico; Wei, Xiaoling; Slade, Alan; Abrams, Ken; Martini, Alberto
Abstract : Background: Canakinumab (CAN), a selective, human anti-IL-1β mAb, has shown sustained therapeutic effect along with corticosteroid (CS) dose reduction/discontinuation in patients (pts) with systemic juvenile idiopathic arthritis (SJIA), in a long-term extension study (NCT00891046 ). 1 Objectives: To evaluate the efficacy and safety of 2 different CAN tapering regimens in SJIA pts who were in clinical remission (NCT02296424 ). Methods: This Phase 3b/4 study had 2 parts. Of 182 enrolled pts, 166 pts with inactive disease (ID) (cohort 1; 68pts) 1 and CAN-naïve pts (cohort 2; 98pts) were administered subcutaneous CAN 4mg/kg q4w in Part I. Per protocol titration off CS and/or methotrexate (MTX) was attempted during Part I. Eligible pts (ID for 24 weeks[wks] and being CS- and MTX-free for at least 4 wks) advanced to Part II wherein, pts were randomised to either a 3-step CAN dose reduction (2mg/kg/q4w, followed by tapering to 1 mg/kg/q4w and then discontinuation) or dose interval prolongation (4mg/kg q8w, followed by tapering to 4mg/kg/q12w and then discontinuation); pts advanced to the next tapering step if ID was maintained for 24 wks. Adapted American College of Rheumatology (ACR) paediatric criteria, its individual components and Juvenile Arthritis Disease Activity Score (JADAS) were assessed. Results: In total, 75 pts were randomised to a dose reduction (n=38) or dose interval prolongation (n=37) CAN tapering regimen in part II. The pts who maintained ID for 24 wks exceeded the predefined threshold of 40% for the reduced CAN dose arm (71%) and prolonged dose interval (84%) treatment arm of Step 1 (primary endpoint). A total of 68.4% (26/38) and 81.1% (30/37) pts in the dose reduction and interval prolongation arms, respectively were successful in Step 2; 33% (25/75) of pts successfully discontinued CAN and maintained ID for 24 wks. ID, ACR 90/100 and JADAS 27 C-reactive protein (CRP) scores are summarised in the table. Adverse events (AEs) and serious AEs observed within the 2 cohorts and across Parts I and II were similar. The most frequent AEs were common infections (nasopharyngitis, upper respiratory tract infection, pharyngitis) followed by SJIA-related events (rash, pyrexia and arthralgia). Conclusion: SJIA pts with ID for 24 wks on CAN monotherapy can successfully taper CAN by either reducing the dose or prolonging the dosing interval. However, only a minority of pts overall successfully discontinued CAN treatment and maintained ID for 24 wks. The safety profile was similar and consistent with other CAN SJIA studies. No new safety signals were identified. Reference: [1] Arthritis Rheumatol.2016; 68 (S10). Disclosure of Interests: Pierre Quartier Consultant for: AbbVie, Chugai-Roche, lilly, Novartis, Novimmune, Sanofi, and SOBI, Consultant for: AbbVie, Chugai-Roche, Lilly, Novartis, Novimmune, Sanofi, and SOBI, Speakers bureau: AbbVie, BMS, Chugai-Roche, Novartis, Pfizer, and SOBI, Speakers bureau: AbbVie, BMS, Chugai-Roche, Novartis, Pfizer, and SOBI, Ekaterina Alexeeva: None declared, Carine Wouters Grant/research support from: Grant/research support to Istituto Gaslini from GlaxoSmithKline immune-inflammation: unrestricted grant to study Blau syndrome; Roche: unrestricted research grant; Pfizer: grant for psychological care of patients with JIA, Grant/research support from: GSK, Roche, Pfizer, Inmaculada Calvo Grant/research support from: received research grants from Pfizer, Roche, Novartis, Clementia, Sanofi, MSD, BMS and GSK, Consultant for: Advisory boards: Novartis, AbbVie, Speakers bureau: AbbVie, Roche, Novartis, SOBI, Tilmann Kallinich Grant/research support from: Novartis, Speakers bureau: Sobi, Roche, Novartis, CLB, Nico Wulffraat: None declared, Xiaoling Wei Employee of: Novartis, Alan Slade Shareholder of: Novartis Pharmaceuticals Corporation, Employee of: Novartis Pharmaceuticals Corporation, Ken Abrams Shareholder of: Novartis, Employee of: Novartis, Alberto Martini: None declared